The necessity–concerns framework predicts adherence to medication in multiple illness conditions: A meta-analysis. Issue 5 (May 2016) - Foot, Holly; La Caze, Adam; Gujral, Gina; Cottrell, Neil
Highlights: We investigated the relationship between medication beliefs and adherence. Necessity beliefs were significantly positively correlated with adherence. Concern beliefs were significantly negatively correlated with adherence. Necessity effect size was different in asthma and cardiovascular group. Abstract: Objective: This meta-analysis investigated whether beliefs in the necessity and concerns of medicine and the necessity–concerns differential are correlated with medication adherence on a population level and in different conditions. Methods: An electronic search of Web of Science, EMBASE, PubMed and CINAHL was conducted for manuscripts utilising the Beliefs about Medicines Questionnaire and comparing it to any measure of medication adherence. Studies were pooled using the random-effects model to produce a mean overall effect size correlation. Studies were stratified for condition, adherence measure, power and study design. Results: Ninety-four papers were included in the meta-analysis. The overall effect size(r) for necessity, concerns, and necessity–concerns differential was 0.17, −0.18 and 0.24 respectively and these were all significant ( p < 0.0001). Effect size for necessity was stronger in asthma and weaker in the cardiovascular group compared to the overall effect size. Conclusion: Necessity and concerns beliefs and the necessity–concerns differential were correlated with medication adherence on a population level and across the majority of included conditions. The effect sizes were mostly small with a magnitude comparable to other predictors of adherence. Practice implications: This meta-analysis suggests that necessity and concern beliefs about medicines are one important factor to consider when understanding reasons for non-adherence.